2011
DOI: 10.1303/jjaez.2011.227
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Development and Reproduction of Four Cereal Aphid Species Reared on Sorghum or Barley to Evaluate as Alternative Prey for Banker Plant System

Abstract: Intrinsic rates of the natural increase of four cereal aphid species, Melanaphis sacchari (Zehntner), Rhopalosiphum maidis (Fitch), Rhopalosiphum padi (L.), and Schizaphis graminum (Rondani) reared on sorghum or barley were compared in order to evaluate their usefulness as alternative hosts for a banker plant system using predators such as an aphidophagous gall midge, Aphidoletes aphidimyza (Rondani), especially for the use in the hot season. Survivorship curves, total survival period, and fecundity of each ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Lopes-da-Silva et al 2014found an intrinsic rate of increase of M. sacchari on sorghum at 24 °C of 0.30, a much smaller value than the present study found at 25 °C (0.405). We found that r m doubled when the temperature increased from 15 to 25 °C, and the same rate was observed for M. sacchari on sorghum by Abe et al (2011). However, Abe et al (2011) observed that the r m increased from 0.390 at 25 °C to 0.450 under 30 °C, whereas in the present study the r m decreased from 0.405 to 0.124 when the temperature increased from 25 to 30 °C.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Lopes-da-Silva et al 2014found an intrinsic rate of increase of M. sacchari on sorghum at 24 °C of 0.30, a much smaller value than the present study found at 25 °C (0.405). We found that r m doubled when the temperature increased from 15 to 25 °C, and the same rate was observed for M. sacchari on sorghum by Abe et al (2011). However, Abe et al (2011) observed that the r m increased from 0.390 at 25 °C to 0.450 under 30 °C, whereas in the present study the r m decreased from 0.405 to 0.124 when the temperature increased from 25 to 30 °C.…”
Section: Discussionsupporting
confidence: 76%
“…We found that r m doubled when the temperature increased from 15 to 25 °C, and the same rate was observed for M. sacchari on sorghum by Abe et al (2011). However, Abe et al (2011) observed that the r m increased from 0.390 at 25 °C to 0.450 under 30 °C, whereas in the present study the r m decreased from 0.405 to 0.124 when the temperature increased from 25 to 30 °C. At 24 °C, M. sacchari R 0 was 27.70 (Lopesda-Silva et al 2014), while in the present study, M. sacchari population growth from 1 generation to the next was nearly 6 times higher at 25 °C.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Development and reproduction of four cereal aphid species on sorghum and barley allowed for evaluating alternative prey for banker plant systems using the aphid predator aphidophagous gall midge Aphidoletes aphidimyza (Rondani). The results suggested that the combination of sorghum as banker plants and the sugarcane aphid Melanaphis sacchari (Zehntner) as alternative hosts could be suitable for use in hot seasons [17]. Bottom-up effects were evaluated using four cereal plant species with three levels of reproductive performance of R. padi and A. colemani, the most common banker plant system used worldwide.…”
Section: Reproduction Of Natural Enemies On Alternative Food In the Bmentioning
confidence: 99%
“…Thus, the bootstrap method was used to estimate r (Efton 1982). Random sampling and calculation of r were repeated 1000 times by use of Mathematica 5.1 (Wolfram Research 2004, Abe et al 2011. To compare r-values, a Kruskal-Wallis test and a Bonferroni-weighted U-test were conducted, because the distribution calculated by use of the re-sampling method was not guaranteed to produce a normal distribution (Efton 1982).…”
Section: Experiments 3: Lifetime Fecundity and Intrinsic Rate Of Naturmentioning
confidence: 99%